DEPDC1B is a key regulator of myoblast proliferation in mouse and man. (11th December 2019) - Figeac, Nicolas; Pruller, Johanna; Hofer, Isabella; Fortier, Mathieu; Ortuste Quiroga, Huascar Pedro; Banerji, Christopher R. S.; Zammit, Peter S.
Abstract: Objectives: DISHEVELLED, EGL‐10, PLECKSTRIN (DEP) domain‐containing 1B (DEPDC1B) promotes dismantling of focal adhesions and coordinates detachment events during cell cycle progression. DEPDC1B is overexpressed in several cancers with expression inversely correlated with patient survival. Here, we analysed the role of DEPDC1B in the regulation of murine and human skeletal myogenesis. Materials and methods: Expression dynamics of DEPDC1B were examined in murine and human myoblasts and rhabdomyosarcoma cells in vitro by RT‐qPCR and/or immunolabelling. DEPDC1B function was mainly tested via siRNA‐mediated gene knockdown. Results: DEPDC1B was expressed in proliferating murine and human myoblasts, with expression then decreasing markedly during myogenic differentiation. SiRNA‐mediated knockdown of DEPDC1B reduced myoblast proliferation and induced entry into myogenic differentiation, with deregulation of key cell cycle regulators (cyclins, CDK, CDKi). DEPDC1B and β‐catenin co‐knockdown was unable to rescue proliferation in myoblasts, suggesting that DEPDC1B functions independently of canonical WNT signalling during myogenesis. DEPDC1B can also suppress RHOA activity in some cell types, but DEPDC1B and RHOA co‐knockdown actually had an additive effect by both further reducing proliferation and enhancing myogenic differentiation. DEPDC1B was expressed in human Rh30 rhabdomyosarcoma cells, where DEPDC1B or RHOA knockdown promoted myogenic differentiation, but without influencing proliferation. Conclusion: DEPDC1B plays a central role in myoblasts by driving proliferation and preventing precocious myogenic differentiation during skeletal myogenesis in both mouse and human.